2020
DOI: 10.1136/bmjgh-2019-002199
|View full text |Cite
|
Sign up to set email alerts
|

Which men change in intimate partner violence prevention interventions? A trajectory analysis in Rwanda and South Africa

Abstract: IntroductionEmerging evidence suggests working with men to prevent intimate partner violence (IPV) perpetration can be effective. However, it is unknown whether all men benefit equally, or whether different groups of men respond differentially to interventions.MethodsWe conducted trajectory modelling using longitudinal data from men enrolled in intervention arms of three IPV trials in South Africa and Rwanda to identify trajectories of IPV perpetration. We then use multinomial regression to describe baseline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Both trials had their own limitations as described in their primary outcomes papers ( Dunkle et al, 2020 ; Gibbs, Washington, et al, 2020 ) which remain valid for the secondary analyses conducted in this current study. For instance, all measures rely on self-report, making them subject to reporting bias.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Both trials had their own limitations as described in their primary outcomes papers ( Dunkle et al, 2020 ; Gibbs, Washington, et al, 2020 ) which remain valid for the secondary analyses conducted in this current study. For instance, all measures rely on self-report, making them subject to reporting bias.…”
Section: Discussionmentioning
confidence: 78%
“…Results from the main trial analysis found that men in the SS-CF intervention reported significantly less perpetration of severe physical and/or sexual IPV (aOR:0.70, 95% CI: 0.52, 0.94, p < 0.05), physical IPV (aOR:0.71, 95% CI: 0.51, 0.97, p < 0.05) and a non statistically significant reduction in perpetration of sexual IPV (aOR:0.74, 95% CI: 0.54, 1.03, p = 0.07) at 24 months. There was no evidence of an intervention effect on women's experiences of physical and/or sexual IPV ( Gibbs, Washington, et al, 2020 ).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations